État, Politique et absence : le « statut » des Marocains Résidant à l’Étranger (MRE) - Malika Gouirir (Revue des Mondes Musulmans et de la Méditerranée)
Migrants are subject to the public policies of both emigration and immigration countries. By the designation “Moroccans residing abroad”, or “MRE” (Marocains Résidant à l’Etranger), Morocco signals to all of its citizens the existence of a relation of filiation that could never be broken or forgotten. The establishment of rights and specific arrangements has replaced the direct control of migrant populations. The MRE are not always aware of having the benefit of special arrangements. Ignorance of Moroccan law prevents those “silent” MRE from claiming this status. The simultaneous holding of multiple citizenships may lead to conflicts. Such questions, when linked to personal status, shed light on persistent dilemmas on such issues as heritage and the right to vote. The “digital” MRE become “ambassadors” of their “country”. Contemporary social networks can partially compensate their physical absence. The “migrant” is released from the feeling of never being at home. However, the difficulties of the concrete exercise of these rights raise the issue of the political and symbolic existence of this community with its multifarious links to various territories. All of them face the issue of the heritage of property but also of family histories and the “obligation of memory” towards their ancestors buried in Morocco.